2015
DOI: 10.1007/s00204-015-1570-1
|View full text |Cite
|
Sign up to set email alerts
|

Selective cancer-killing ability of metal-based nanoparticles: implications for cancer therapy

Abstract: There has been little focus on the promising ability of metal-based nanoparticles (NPs) to kill cancer cells while sparing normal cells. Many in vitro and in vivo reports suggest that certain metal-based NPs are able to induce apoptosis and autophagy in cancer cells at specific concentrations that are not significantly toxic to non-cancerous cells. Those NPs are thought to exploit the oxidative stress conditions that prevail in cancer cells, which are largely exhausted of antioxidant ability. This review consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 143 publications
(138 reference statements)
0
30
0
Order By: Relevance
“…Evidence are rapidly increasing that manipulation of intracellular ROS production can be utilized in killing of cancer cells without much affecting the normal cells 36 , 39 . Our earlier studies have shown that semiconductor nanoparticles such ZnO have potential to selectively kill cancer cells via ROS generation while sparing the normal cells 37 , 38 , 52 . In the present study, we further investigated the regulation of oxidative stress markers (ROS, SOD & GSH) in HepG2 cells upon exposure to 25, 50 and 100 μg/ml of pure and Ag-doped TiO 2 NPs for 6 h. Intracellular ROS generation was assessed by DCFDA fluorescent probe.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence are rapidly increasing that manipulation of intracellular ROS production can be utilized in killing of cancer cells without much affecting the normal cells 36 , 39 . Our earlier studies have shown that semiconductor nanoparticles such ZnO have potential to selectively kill cancer cells via ROS generation while sparing the normal cells 37 , 38 , 52 . In the present study, we further investigated the regulation of oxidative stress markers (ROS, SOD & GSH) in HepG2 cells upon exposure to 25, 50 and 100 μg/ml of pure and Ag-doped TiO 2 NPs for 6 h. Intracellular ROS generation was assessed by DCFDA fluorescent probe.…”
Section: Resultsmentioning
confidence: 99%
“…30 Induction of cell death by apoptosis is a desired mechanism, as intracellular content is not released to the tissue, avoiding further damage of the host tissues. 39,40 In this study, we used concentrations of LNC or AcE-LNC, which did not cause cell death; however, the uptake of nanocapsules sensitized melanoma cells to apoptosis in serum deprivation and hypoxia, both restrictive conditions found in the tumor microenvironment. 41 It is interesting to mention that concentrations of LNC or AcE-LNC, higher than employed in this …”
Section: Discussionmentioning
confidence: 99%
“…11 In the wake of the rapid development of synthesis techniques, diverse metal nanoparticles (NPs) with unique and outstanding properties have been successfully synthesized and gradually applied in various areas, especially in the life sciences for biosensing, 12,13 cell imaging, 14 drug delivery, [15][16][17] and clinical treatment. 18,19 For example, NPs for targeted delivery have unique capability to localize delivery of drugs to designated tissues. 20 Combining medicines with functionalized NPs may decrease their intrinsic toxicities and improve their therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 99%